EVALUASI JARINGAN DAERAH IRIGASI RAWA PASANG SURUT PALAMBAHEN KABUPATEN PULANG PISAU - Eva Suciyati (Lambung Mangkurat University Press, 2018)
Tidal swamp areas which are mostly wetlands which are often considered marginal land are now considered as land that has the potential to be developed into agricultural land. The Palambahen Tidal Swamp Irrigation Area (DIR) in Pangkoh Hulu Village Pandih Batu District Pulang Pisau Regency with an area of ​​approximately 3,267.30 ha is one of the tidal DIRs that has the potential to be developed. The existing problem is the condition of the channel that is not functioning properly so it needs to be evaluated on the condition of the network by evaluating the performance of the existing network so that actions will be taken to improve the performance of the network. In addition, it is also necessary to study the type of land unit and the suitability of the land available at that location. The assessment can be based on the results of the assessment on the condition of the canals, buildings and protective dykes. The results showed that the DIR Palambahen obtained a network condition index of 1.15 and a 72.36% network function, which means that the performance of the Palambahen tidal swamp reclamation network is in the good category category and recommendations for handling are periodic maintenance. For land units The DIR Palambahen is included in the VIII land unit covering 355.30 ha and IX land unit in 2893.53 ha. Land suitability in the Palambahen Tidal DIR is for an appropriate paddy field (S1) covering an area of ​​1,584.57 ha and quite suitable (S2) covering an area of ​​1682.73 ha, for an upland rice crop quite suitable (S2) covering an area of ​​3,267.30 ha, for a crop palawija suitable (S1) covering 415.01 ha, quite suitable (S2) covering 2,145.18 ha and marginal suitable (S3) covering 707.11 ha, and for suitable annual plants (S1) covering 562.47 ha and quite suitable (S2) covering an area of ​​2,704.83 ha.